Perkembangan historis dan makna simbolik kaligrafi islam di masjid-masjid kuno nusantara abad ke-15 hingga ke-19 - malikha, hilda himmatul (Maliki Interdisciplinary Journal, 2026)
This research is titled " The Historical Development and Symbolic Meaning of Islamic Calligraphy in Ancient Mosques of the Indonesian Archipelago from the 15th to the 19th Century AD " and aims to uncover the development of Islamic calligraphy art in Nusantara and understand the symbolic meaning contained within it. The art of calligraphy in Islam serves not only as an esthetic element but also as a medium for proselytization and the representation of deep spiritual values. Thru historical and descriptive studies, this research analyzes the form, style, and symbolic meaning of calligraphy ornaments found in several ancient mosques such as the Demak Grand Mosque, the Kudus Minaret Mosque, the Banten Grand Mosque, the Katangka Mosque in Gowa, and the Indrapuri Mosque in Aceh. The research method used is a qualitative approach with library research, which involves examining various sources such as books, scientific journals, photo documentation, and historical archives. The research results show that the calligraphy ornaments in ancient Nusantara mosques are the result of acculturation between Islamic art and local culture. The Arabic script used not only conveys religious messages but also reflects the philosophy of monotheism, balance, and harmony with nature. The calligraphy in those mosques has become a beautiful, peaceful, and inclusive symbol of Nusantara Islamic identity.